2016
DOI: 10.4178/epih/e2016008
|View full text |Cite
|
Sign up to set email alerts
|

Social factors associated with psychological states among tuberculosis management nurses

Abstract: OBJECTIVES:This study examined job satisfaction, empowerment, job stress, and burnout among tuberculosis management nurses and physicians in public healthcare institutions.METHODS:This was a cross-sectional study analyzing survey data collected from 249 nurses and 57 physicians in 105 public health centers, three public tuberculosis hospitals, and one tertiary hospital. The survey questionnaire comprised general characteristics, work-related characteristics, and four index scales (job satisfaction, empowerment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Second, departmental records can quantify medications and supplies and confirm that stock meets institutional demands for best practices. Third, by increasing the number of HCWs per work shift and distributing responsibilities, overall job stress and burnout can be reduced (29). Fourth, monetary or legal sanctions for failed adherence to recommended infection control practices could underscore critical changes in the organizational culture within the health institution that prioritize HCWs' physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Second, departmental records can quantify medications and supplies and confirm that stock meets institutional demands for best practices. Third, by increasing the number of HCWs per work shift and distributing responsibilities, overall job stress and burnout can be reduced (29). Fourth, monetary or legal sanctions for failed adherence to recommended infection control practices could underscore critical changes in the organizational culture within the health institution that prioritize HCWs' physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that providers who were dissatisfied with their workload were three times more likely to be dissatisfied with their current job. A heavy workload, most often due to the shortage of health workers (the majority being women), cuts the time that would otherwise be available for family duties and recreation, in turn increasing their risk of stress-related morbidity, absenteeism and burnout [ 17 ]. Thus, apart from inadequate salary and supplies [ 43 , 46 ], a heavy workload [ 46 , 47 ] and an unfavourable working environment [ 48 , 49 ] are important reasons for job dissatisfaction and attrition of health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The understaffing leads to long queues and increased staff workload, which makes it difficult to efficiently counsel the patients and track the defaulters [ 16 ]. Higher workload in already overburdened health systems in resource-limited countries have been linked to a negative effect on health care provider job satisfaction [ 17 , 18 ], especially if the resulting additional tasks and responsibilities are not coupled to incentives [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that anger -management training can influence job satisfaction although we could not find any research in this regard to evaluate our hypothesis. But, since previous findings including [ [14][15][16]26] have shown that job satisfaction is affected by aggression especially in psychiatric wards we assumed that anger-management training can increase job satisfaction. This hypothesis was confirmed by findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' aggression has also unpleasant consequences for patients, their family and health care system [14]. It may disturb their interpersonal relationships and decrease their job satisfaction [15,16] as one of the most important effective factors on declining the quality and working efficiency in nurses [17,18] and the main factor of turnover in different countries' nursing system [19][20][21]. Job satisfaction is affected by various factors including working condition, communication skills [22], salary, type of hospital or the ward working in [23], age, marital status, recruitment status [24], emotional intelligence [25] and occupational stress [26].…”
Section: Introductionmentioning
confidence: 99%